Pencemaran Nama Baik dalam Tinjauan Hukum Islam - Rizqi, Retanisa; Wati, Sela Saras (IAIN Metro, 2024)
Any verbal or written conduct that breaches the law is considered to be a defamatory act, which spreads false information to the public and assaults a person's honor by disseminating the information to the general public, which can injure the party in question and harm the person's good name or reputation. Last but not least, according to Fiqh Jinayah, the unlawful act of defamation falls within the category of ta'zir punishment, which the court determines as bearing legitimacy in the context of sentencing. Defamation on social media is a crime because it is not covered by Islamic criminal law and is not addressed in the Qur'an or hadith. It is included in the ta'zir finger category. Ta'zir punishment is intended to prevent or delay the arrival of a disaster, with the authority of the ruler or judge over the administration of punishment for the general public.